An open trial investigation of Treatnet Family among adolescents with substance use problems. (December 2021) - Busse, Anja; Kashino, Wataru; Suhartono, Sanita; Narotama, Narendra; Pelupessy, Dicky; Irwanto,; Essau, Cecilia A.
Highlights: Treatnet Family (TF) had a positive significant impact in reducing alcohol use. After participating in the TF, the adolescents were engaged with significantly fewer friends who consumed substances and participated in antisocial behaviours. The two most reported life events (i.e., "got in a lot of arguments or fights" and "had problems with drugs or alcohol") before the intervention were significantly decreased at the follow-up assessment. Based on parent's/family member's reports, there was a significant decrease in mental health problems across time. Abstract: Introduction: Studies that used evidence-based family therapies have demonstrated significant effects in reducing adolescent drug use and delinquent behaviours, and in reducing comorbid mental health problems. However, almost all these studies were conducted in high-income countries. The overall aim of the present study was to explore the effect of United Nations Office on Drugs and Crime's (UNODC) Treatnet Family (TF) in reducing substance consumption, drug-related activities, reducing mental health problems, and in improving family interaction among adolescents with substance-use problems. Method: Nineteen adolescents who had been referred to a community counselling clinic because of substance-use problems and their parents/family members participated in TF. They completed a set of questionnaires to measure substance use, family functioning, mental health problems, and life events at pre-, post-intervention as well as at a one month-follow-up assessment. Results: TF had a positive significant impact in reducing alcohol use among adolescents with substance-use problems. The number of adolescents who smoked cigarettes and marijuana, and used amphetamines reduced across time. After participating in TF, the adolescents were involved with significantly fewer friends who consumed substances and participated in antisocial behaviours. Furthermore, parent/family member reported a significant decrease in mental health problems, and positive changes in adolescent's behaviours. Conclusion: The TF had a positive impact in reducing alcohol consumption and problems related to substance consumption among adolescents with substance-use problems when delivered by practitioners in routine community settings.